Cinchona Alkaloid Catalyzed Asymmetric Desymmetrization of meso‐Cyclic Anhydrides: The Origins of Stereoselectivity. Issue 24 (4th November 2015) - Dedeoglu, Burcu; Catak, Saron; Yildirim, Asli; Bolm, Carsten; Aviyente, Viktorya
Abstract: The asymmetric desymmetrization of meso ‐cyclic anhydrides catalyzed by the pseudoenantiomeric pairs of cinchona alkaloids, quinine (QN) and quinidine (QD), has been subjected to a computational study employing density functional theory (DFT) to understand the origin of the experimentally observed stereoselectivity. The spatial placement of the catalyst with respect to the anhydride, which resembles a molecular tweezer, was found to be the primary reason for the stabilization of the oxyanion forming in the transition states, as well as the oxyanion intermediate observed along the reaction coordinate. The distortion–interaction model has been employed to rationalize the experimentally observed enantiomeric ratios. The assistance of solvent molecules was essential in the prediction of experimental enantioselectivities. Abstract : Stereochemical origins : The asymmetric desymmetrization of meso ‐cyclic anhydrides catalyzed by the pseudoenantiomeric pairs of cinchona alkaloids, quinine and quinidine, has been subjected to a computational study employing density functional theory to understand the origin of the experimentally observed stereoselectivity.